Determinants of Foreign Exchange Reserve of Emerging Economy: Time Series Evidence from Bangladesh - Naima, Jannatul; Mony, Puja Das; Lalon, Raad Mozib (International Journal of Economics and Financial Issues, 2024)
This paper contributes to existing literatures through investigating the elements influencing Bangladesh’s foreign exchange reserves covering the period from 1972 to 2023. In fact, this study analyzes the impact of several macroeconomic variables, including exports, imports, economic growth, trade balance, remittances, external debt, foreign direct investment (FDI), broad money, real interest rates, exchange rates, and trade openness, using an ordinary least squares (OLS) regression model on the foreign exchange reserves. The findings demonstrate that while trade balance, real interest rates, and trade openness show negative connections, exports, imports, economic growth, remittances, foreign debt, FDI, and broad money have major positive influence on the reserves. With a R2 value of 0.9877, the model shows a great explanatory power and indicates that the chosen variables almost completely explain the variance in foreign exchange reserves. Without the evidence of heteroscedasticity, multicollinearity, or autocorrelation, diagnostic tests validate the robustness of the model. The results highlight the need of keeping balanced trade policies and supporting favorable conditions for exports, remittances, and FDI to guarantee a steady buildup of foreign exchange reserves, thereby ensuring Bangladesh’s economic resilience and stability.